2015
DOI: 10.2147/oajsm.s83159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D and quercetin, alone and in combination, on cardiorespiratory fitness and muscle function in physically active male adults

Abstract: IntroductionVitamin D and the antioxidant quercetin, are promising agents for improving physical performance because of their possible beneficial effects on muscular strength and cardiorespiratory fitness.PurposeThe purpose of this study was to determine the effects of increased intakes of vitamin D, quercetin, and their combination on antioxidant status, the steroid hormone regulators of muscle function, and measures of physical performance in apparently healthy male adults engaged in moderate-to-vigorous-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…All the eight studies conducted for meta‐analysis were published in English and were double‐blind RCTs. However, two of the double‐blind studies were factorial design (Saha & Goswami, ; Scholten et al, ). All the trials were published from 2008 to 2018.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the eight studies conducted for meta‐analysis were published in English and were double‐blind RCTs. However, two of the double‐blind studies were factorial design (Saha & Goswami, ; Scholten et al, ). All the trials were published from 2008 to 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Change in TT concentration after vitamin D supplementation was assessed in eight studies containing 10 effect sizes with 1,061 participants (Heijboer et al, ; Jorde et al, ; Lerchbaum et al, ; Lerchbaum et al, ; Pilz et al, ; Saha & Goswami, ; Scholten et al, ; Zittermann et al, ). The overall effect of meta‐analysis showed no significant effect of vitamin D on TT (WMD = 0.20, 95% CI: −0.20, 0.60, p = 0.336), and heterogeneity ( I 2 = 0.0%, p = 0.508) was not observed among the studies (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The intake of antioxidative compounds such as vitamin C may theoretically mask the suggested pro‐oxidative effects of quercetin. In human intervention studies, pro‐oxidative effects of quercetin were not found with quercetin doses at 500–1000 mg d –1 applied for 3–12 weeks ( n Q = 6–333), but it is still an open question whether quercetin may exhibit pro‐oxidative effects in the human body, especially after a long‐term use of high quercetin doses …”
Section: Safety Aspectsmentioning
confidence: 99%
“…The intake of antioxidative compounds such as vitamin C may theoretically mask the suggested pro-oxidative effects of quercetin. In human intervention studies, pro-oxidative effects of quercetin were not found with quercetin doses at 500-1000 mg d -1 applied for 3-12 weeks (n Q = 6-333), [55][56][57][58][59] but it is still an open question whether quercetin may exhibit pro-oxidative effects in the human body, especially after a long-term use of high quercetin doses. [30,60,61] In general, oral intake of quercetin in humans seems to be well tolerated and only a very low incidence of adverse effects has been observed to date (for details see Supporting Information Table S1).…”
Section: Information From Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation